Unified SER Performance Analysis and Improvement for Multiuser MIMO Downlink with Correlation Rotation Linear Precoding - Liu, Zu-Jun; Wang, Jie-Ling; Sun, De-Chun; Yi, Ke-Chu (IEEE transactions on wireless communications, 2013)
In multiuser multiple-input multiple-output (MIMO) downlink communications, system performance suffers from multiuser interference (MUI). Contrary to common practice where MUI is suppressed, correlation rotation (CR) linear precoding makes MUI constructive via rotating the angle of correlation between transmitted symbols. With the derived closed-form instantaneous SINR expression, we analyze the unified SER performance for CR precoding, and identify the channel condition under which the MUI exploitation via CR precoding will fail and consequently lead to the unified SER performance degradation. To solve the problem, two power allocation schemes that are subject to power constraint are proposed: one is iterative scheme that directly minimizes the unified SER, and the other has a closed-form solution that maximizes the minimum user SINR. The asymptotic behavior and computational complexity of the proposed schemes are analyzed. Numerical and simulation results show that both schemes can avoid the degradation of unified SER performance and furthermore offer performance gains. Moreover, the closed-form solution with much lower complexity can provide a comparable performance to that of the iterative scheme.